German reception of Janusz Korczak - KOWAL, Grzegorz (Transfer. Reception Studies, 2016)
German reception of Korczak is a complex process extending over a long period of time. It can be argued that the representatives of German science and art look for and find creative inspiration in Korczak as if in response to the interest in German culture he expressed. It is enough to recall that after graduating from medical school, Korczak went to Berlin for nine months in order to gain the necessary experience and broaden his knowledge of the latest methods of feeding and baby care. When one looks at the whole process of how Korczak’s ideas spread into German culture, a couple of dates need to be mentioned. As early as in 1935, the first book by Korczak, Bankructwo małego Dżeka (Bankruptcy of Little Jack), is translated into German. In 1957, the translation of perhaps the most popular book by Korczak Król Maciuś Pierwszy (King Matt the First) appears. Interestingly enough, it is published in Warsaw. In the same year, the premiere of Erwin Sylvanus’ play Korczak i dzieci (Korczak and the children) takes place. The translation goes unnoticed, while the play effectively promotes the life and work of the ‘Old Doctor’. The real breakthrough happens, how-ever, in 1972 when ‘Pestalozzi from Warsaw’ was posthumously awarded the Peace Prize of German Booksellers. The news hit the headlines, and a real avalanche of articles dedicated to him swept through German press. Henceforth, Korczak gains the status if a symbol and authority in Germany. This process is crowned by two events: collective edition of Korczak’s works (1996-2010, 16 volumes) and the classification of the author as a German memorial site in the first volume of the compendium Deutsch-Polnische Erinnerungsorte edited by Hahn and Traba (Paderborn 2015).